Influencia De Los Métodos De Enseñanza En El Desarrollo De Habilidades Y Destrezas De Razonamiento Lógico De Los Estudiantes Del Bachillerato General Unificado De La Unidad Educativa "Montalvo", De La Parroquia La Esmeralda Del Cantón Montalvo, Prov De Los Ríos. - Padilla Gaibor Meri Araceli (2015)
The practice of teaching in our country and in any sphere of the planet marks a dynamic practice and constant change, where teachers must be constantly prepared to accept them, using continuous training as the best strategy. For some years, the graduates coming out of media training institutions have had to go through a period of assessment skills, proposed by the National Secretariat of Science and Technology, to obtain a quota in higher education. This new process and its results generated specifically that schools begin to think about how important the development of these skills and abilities, and especially logical reasoning. This situation led us to investigate the importance of logical reasoning, and how they develop in our students; akin to provide them with better conditions to face their future education. And besides this work provides concrete strategies for teachers responsible as we engage in this beautiful task that generated so much good for our students.